Penanggulangan Risiko Bencana di Sekolah Inklusif Kota Tomohon - Aldjon Nixon Dapa (Peneliti.net, 2021)
Tomohon City is one of the areas in North Sulawesi with the potential for frequent disasters, such as Lokon volcanic eruptions, landslides, floods, droughts, hurricanes, earthquakes, non-natural disasters (Covid-19). Of course, this situation threatens the lives of residents, including children with special needs (ABK) who attend inclusive schools in Tomohon City, have the same rights as other children to know about how to protect and save themselves when a disaster occurs. In addition, crew members are one of the most vulnerable groups when a disaster occurs. Some of them have mobility barriers to carry out protection and even self-rescue independently. Hence the need for a Model Guide for Disaster Risk Management in Inclusive Schools, to guide the school community in taking action in the event of a disaster. The research method used is Research and Development (R&D) research. The results showed that the model guide should contain information on how to rescue procedures/plans for ABK who need help from people around them, for example: teachers, friends, and school staff. The presence of a model guide is very much needed, because treating crew members when a disaster occurs must be a super priority to be saved.